2007
DOI: 10.1007/s10800-007-9396-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviour of benzylamine, 2-phenylethylamine and 4-hydroxyphenylethylamine at gold. A comparative study

Abstract: The electrooxidation of benzylamine, 2-phenylethylamine and 4-hydroxyphenylethylamine (tyramine) at a gold electrode in contact with an alkaline electrolyte solution was studied. The effect of amine concentration, electrolyte pH and potential scan rate on the electrooxidation was analysed. The adsorption of amines on the goldsolution interface was found to play a significant role in the oxidation mechanism. The rate determining step was the heterogeneous dehydrogenation of the amine molecule, involving electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The ratio of m/n at ERGO/GCE was calculated to be approximately 1, suggesting that the equal numbers of protons and electrons were transferred in both electrochemical oxidation reactions of OA and TA. The results were consistent with the reported electrochemical mechanism that three protons and three electrons are involved in the electrochemical oxidation of OA and TA [ 26 , 48 , 49 ]. Figure 5 illustrates a possible process for electrochemical oxidation of OA and TA at the surface of ERGO/GCE.…”
Section: Resultssupporting
confidence: 92%
“…The ratio of m/n at ERGO/GCE was calculated to be approximately 1, suggesting that the equal numbers of protons and electrons were transferred in both electrochemical oxidation reactions of OA and TA. The results were consistent with the reported electrochemical mechanism that three protons and three electrons are involved in the electrochemical oxidation of OA and TA [ 26 , 48 , 49 ]. Figure 5 illustrates a possible process for electrochemical oxidation of OA and TA at the surface of ERGO/GCE.…”
Section: Resultssupporting
confidence: 92%
“…The CBMs of ZrS 3 , ZrSS 2-x (15), and ZrS 1-y S 2-x (15/100) are higher than the potential for two-electron reduction of O 2 . Previous studies have shown that the oxidation potential of benzylamine lies higher than that of water, and the benzylamine oxidation was thus used to replace oxygen evolution reaction to couple with photocatalytic and electrocatalytic hydrogen evolution reaction 14 , 17 , 55 , 56 . This suggests the VBM of defective ZrS 3 NBs lying far below the oxidation potential of benzylamine, indicating that these photocatalysts are applicable to the photocatalytic O 2 reduction and benzylamine oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Then dry electrodes were located into clean the three-compartment electrochemical cell separated by glass frits which was used in electrochemical measurements. Electrochemical activation of the bare polycrystalline gold electrode was carried out as described earlier [47]. All measurements described were made at room temperature using solutions deoxygenated by 99.998% argon.…”
Section: Electrodesmentioning
confidence: 99%